(untitled) (Journal of National Institute of Neurosciences Bangladesh, 2025)
Background: Bilateral lumbar micro foraminotomy and bilateral micro-discectomy is considered as a gold standard surgical technique for the treatment of patients with lumbar disc hernia (LDH) with lateral recess stenosis (LRS) although various types of treatment are being developed. Objective: This study aimed to investigate the safety and efficacy of bilateral lumbar micro-foraminotomy and bilateral micro-discectomy for the treatment of patients with lumbar disc hernia (LDH). Methodology: This was a retrospective cohort study conducted in the Department of Neurosurgery & Neuro-ICU at Enam Medical College & Hospital, Savar, Dhaka during the period of January 2019 to December 2020. All data were collected from patient files. Data were collected pre-designed data collection sheet. Results: This study shows shows maximum (48.1%) were 41 to 50 years followed by 37.0% were 31 to 40 years and 14.8% were 20 to 30 years. The average age was 39.66±9.25 years. Majority (77.8%) were male and 22.2% cases were female. The most common levels affected by soft disc prolapse recess stenosis are L4-5 and L5-S1 segments. This study shows the mean Oswestry Disability Index (ODI) were 76.11±12.81 in preoperative and 5.00±7.72 postoperative. The decrease in values has been found to be significant in preoperative and postoperative (P<0.001). Study found only 3.7% was complications. Conclusion: Bilateral lumbar micro foraminotomy and bilateral micro-discectomy is an effective and safe method in the treatment of soft disc prolapse with lateral recess stenosis as it has low complication rates. Journal of National Institute of Neurosciences Bangladesh, January 2024;10(1):17-20